Topical lidocaine and or/ intravenous midazolam before radial coronary angiography to prevent radial artery spasm - Mohamed Zakariya Elattar; Reda Biomy Bastwisy; Wael Anwar Haseeb; Mohamed Kamal Salama (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the possible advantage of topical lidocaine and intravenous midazolam in preventing spasm and pain related to the radial artery. Methods: The prospective, comparative study was conducted at the catheterization laboratory of the cardiology department Kafrelsheikh University Hospital, Egypt, from January 2021 to January 2022, and comprised adult patients of either gender who were due to undergo coronary angiography and/or percutaneous coronary intervention for different indications. The patients were randomised control group I which was administered a cocktail of nitroglycerine, verapamil and heparin, intervention group II which was administered the control cocktail plus topical lidocaine, group III which was administered the control cocktail plus midazolam intravenously, and group IV which was administered the control cocktail plus topical lidocaine and intravenous midazolam. The groups were compared for frequency of radial artery spasm, access site cross-over and the difference in occurrence as well as procedure events, including the puncture number, time and complications. Data was analysed using SPSS 25. Results: Of the 120 patients, there were 30(25%) in each of the 4 groups. Overall, there were 72(60%) males and 48(40%) females. Gender and mean age were not significantly different among the groups (p>0.05). Spasm of the radial artery occurred in 22(18.3%) patients, with higher incidence in the group I 12(40%). The median visual analogue scale score was higher in patients with radial artery spasm patients (p<0.001). The groups showed no significant differences in terms of frequency related to ad hoc percutaneous coronary intervention, contrast volume and fluoroscopy time (p>0.05), while they showed a significant difference in puncture time (p<0.05). Significant differences were noted among the groups in the incidence of radial artery spasm, visual analogue scale scores, requirement of multiple punctures, and the number of indicated punctures (p<0.05). Access site cross-over was more in the group I, while age, complication rates, visual analogue scale score, incidence of multiple punctures, and puncture time were significantly higher in patients with radial artery spasm (p<0.05). Conclusion: Cutaneous analgesia and procedural sedation before transradial access for coronary interventions were found to be associated with a substantial reduction in radial artery spasm and procedure-related discomfort. Keywords: Coronary intervention, Transradial access, Radial artery spasm, Topical lidocaine, Intravenous midazolam